Answer:
Sam is correct
Step-by-step explanation:
The third side is the one with greatest length. To make a triangle the other two lengths have to be greater than the greatest one when combined.
Hope this Helps.
Answer:
<h3>(-4, 1)</h3>
Step-by-step explanation:
-x-3=y, therefore x = -y-3
-3x - 8y = 4
Find the value of y
Substitute the x in -3x - 8y = 4 with -y-3
We get
-3·(-y-3) - 8y = 4
3y + 9 - 8y = 4
-5y = 4-9
-5y = -5
<h3>y = 1</h3>
_______________
Find the value of x
x = -y-3
x = -1-3
<h3>x = -4</h3>
_______________
Answer (x, y) =
<h3>(-4, 1)</h3>
_____________________
#IndonesianPride - kexcvi
Answer:
10/3, or 3 1/3.
Step-by-step explanation:
3/1 + 1/3
3 + 1/3
9+1/3
10/3, or 3 1/3.
For an investment compounded continuously, the rule of 69 gives a better approximation than the rule of 72 (for normal compound interests).
Answer:
because when the value of x is replaced in the factorisation it Will be equivalent to 100